A Cross-Sectional Study on the Association between Acyanotic Congenital Heart Disease and Cognitive Function in Children at Adam Malik Hospital Medan (2022–2023) - Aqilah Halwa Subrata; Tina Christina Lumban Tobing; Mustafa Mahmud Amin; Dina Arwina Dalimunthe (Talenta Publisher, 2026)
Background. Congenital Heart Disease (CHD) has become the primary health issue for newborns. Children with CHD who experience the most complications are those with acyanotic CHD. Children with acyanotic CHD experience many clinical disturbances such as shortness of breath, recurrent respiratory infections, cyanosis, and inadequate nutrition intake. This makes children with acyanotic CHD have a higher risk of experiencing cognitive developmental disorders compared to other normal children. Objective. This study aims to examine the correlation between acyanotic CHD and cognitive function in children at Adam Malik Hospital in 2022–2023. Method. An observational analytic study with a cross-sectional design. The subjects of this study are pediatric patients with acyanotic CHD. Data were obtained from the Denver Developmental Screening Test II cognitive function medical records of 46 patients at Adam Malik Hospital in 2022–2023. Data analysis was conducted using the chi-square hypothesis test. Results. This study involved 46 patient samples with acyanotic CHD. The chi-square test results showed no significant correlation between acyanotic CHD and meaningful cognitive function (p-value = 0.462), where acyanotic CHD did not significantly affect gross motor, fine motor, language, and personal–social functions in children. Conclusion. There is no significant correlation between acyanotic CHD and cognitive function in children at Adam Malik Hospital Medan in 2022–2023. Keyword: Acyanotic, children, cognitive function, congenital heart disease, denver developmental screening test II Latar Belakang: Penyakit Jantung Bawaan (PJB) menjadi masalah kesehatan yang paling utama pada anak yang baru lahir. Anak dengan PJB yang paling banyak mengalami gangguan adalah anak dengan PJB asianotik. Anak dengan PJB asianotik mengalami banyak gangguan klinis seperti sesak napas, infeksi saluran napas berulang, sianosis, dan nutrisi yang tidak adekuat. Hal ini membuat anak dengan PJB asianotik memiliki risiko yang lebih tinggi untuk mengalami gangguan perkembangan kognitif dibandingkan dengan anak normal lainnya. Tujuan: Penelitian ini untuk mengetahui hubungan antara PJB asianotik dengan fungsi kognitif pada anak di Rumah Sakit Adam Malik Medan tahun 2022–2023. Metode: Penelitian ini menggunakan metode analitik observasional dengan desain studi cross sectional. Subjek pada penelitian ini adalah pasien anak dengan PJB asianotik. Data diperoleh dari rekam medis fungsi kognitif Denver Developmental Screening Test II sebanyak 46 pasien di Rumah Sakit Adam Malik Medan tahun 2022–2023. Analisis data dilakukan dengan uji hipotesis chi-square. Hasil: Penelitian ini melibatkan 46 sampel pasien dengan PJB asianotik. Hasil uji chi-square menunjukkan tidak ada hubungan signifikan antara PJB asianotik dengan fungsi kognitif yang bermakna (p-value = 0.462), dimana PJB asianotik tidak berpengaruh signifikan terhadap fungsi motorik kasar, motorik halus, bahasa, dan personal–sosial pada anak. Kesimpulan: Tidak terdapat hubungan yang signifikan antara PJB asianotik dengan fungsi kognitif pada anak di Rumah Sakit Adam Malik Medan tahun 2022–2023. Keyword: Anak, asianotik, denver developmental screening test II, fungsi kognitif, penyakit jantung bawaan